MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMA KELAS XI MENGGUNAKAN PENDEKATAN PEMBELAJARAN BERBASIS MASALAH PADA MATERI LINGKARAN - Hamka, Muhamad; Jalaludin, Muhamad; Rohaeti, Euis Eti; Afrilianto, M (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study aims to examine and analyze about problem based learning approach to improve understanding ability in senior high school . The population in this research is XI IPA grade senior high school in Karawang. This study was designed qualitative descriptive method. Based on the results and discussion students understanding ability had improved. Based on the results of the analysis and discussion, it can be concluded that students' mathematical understanding on the subject matter "circle" of students in grade XI IPA 3 SMAN 6 Karawang can be improved by using problem-based learning approach. It is known from the number of students who experience improvement in each cycle. In cycle I shows that the result of learning mathematics on the matter of classical equation of the circle score obtained by students from the questions given in the first cycle test, obtained 30 students reached 66.67% of 45 students who are able to get the value of 76 and above while in cycle II shows that the results of mathematics learning on the material of tangent tangent similarity has reached 91.12% or as many as 41 students.Â